2013
DOI: 10.1089/dia.2013.0074
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic Insulin Aspart 30 in Insulin-Naive People with Type 2 Diabetes in Non-western Nations: Results from a Regional Comparative Multinational Observational Study (A1chieve)

Abstract: Insulin-naive people with T2DM beginning aspart premix insulin in routine clinical practice in non-western nations had clinically useful improvements in blood glucose control after 24 weeks in all seven regions. Improvements from baseline for glucose control variables were greater than cross-regional differences in those variables at 24 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…A common problem recorded was the poor degree of metabolic control (HbA1c ≈ 8 %), that coincides with data reported consistently in previous studies [ 7 , 9 , 10 , 30 ].…”
Section: Discussionsupporting
confidence: 90%
“…A common problem recorded was the poor degree of metabolic control (HbA1c ≈ 8 %), that coincides with data reported consistently in previous studies [ 7 , 9 , 10 , 30 ].…”
Section: Discussionsupporting
confidence: 90%
“…In addition, switching from human insulin to premix analogues showed a similar positive safety profile. Evidence suggests that in insulin-naïve African subjects with T2DM, initiating once-daily premix insulin with or without OADs achieved better glycemic control than when compared with human insulin [ 90 ]. In a systematic review, short-term intensive insulin therapy was reported to improve the underlying pathophysiology in newly diagnosed T2DM.…”
Section: Type 2 Diabetes Mellitus (T2dm)mentioning
confidence: 99%